Cyber value stream system reduced waste and non-value added of manufacturing operation - Ahmad, A.N. Aizat; Hasan, Sulaiman; Husin, Nofafifah (Institute of Research Engineers and Doctors, USA, 2015)
Lean manufacturing becomes popular as a beneficial way in the pursuit of better system efficiencies in manufacturing environment. Value stream mapping (VSM) was one of the methods that can be used by practitioner to support lean. VSM method is also a simple and straightforward method to identify waste and determined causes of the waste through the value stream mapping method and propose solutions to improve workplace environment. This project is an attempt to computerize the process through the application of VSM. Computerize value stream system (CVSS) is basically a method which is an internet networking system combining with traditional concept of value stream mapping method to be used at manufacturing company to reduce wastes. This paper summarizes the way to apply an internet, online and network based of an efficient computerize value stream system to improve operation value of the manufacturing company. This paper reviews the design of the package that will replace the manual method of doing VSM. The system is tested in a real shop floor environment.